2022
DOI: 10.1186/s12891-022-05863-z
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of coronal vertebral and IVD wedging to Cobb angle changes in adolescent idiopathic scoliosis during growth

Abstract: Study design Prospective study Background Vertebral and intervertebral disc (IVD) wedging are often seen in patients with adolescent idiopathic scoliosis (AIS). However, the relationship between wedging and curve progression, and the change of wedging before bracing to final weaning is unknown. The aim of this study was to investigate the pattern and sequence of vertebral and IVD wedging development, and to determine the relationship between the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…While there is no universally accepted theory explaining the pathogenesis of AIS, anterior column overgrowth is a frequently studied phenomenon, [69][70][71][72][73][74][75] with ongoing debate surrounding the cause-effect relationship with wedging and rotation. 76,77 Our included studies also reported sagittal wedging in lower junctional vertebrae and discs, which was associated with increases in Cobb angle.…”
Section: Sagittal Deformitymentioning
confidence: 99%
“…While there is no universally accepted theory explaining the pathogenesis of AIS, anterior column overgrowth is a frequently studied phenomenon, [69][70][71][72][73][74][75] with ongoing debate surrounding the cause-effect relationship with wedging and rotation. 76,77 Our included studies also reported sagittal wedging in lower junctional vertebrae and discs, which was associated with increases in Cobb angle.…”
Section: Sagittal Deformitymentioning
confidence: 99%